La resolución de problemas: una revisión estructurada - Perales Palacios, F. Javier (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
The aim of this paper is to review and organize the background, historic development and present situation of problem-solving research on Sciences and Mathematics.